Volley Game Side Step and Cross Step Block Movement Ability of Male PGRI Mnelalete High School Students - Runesi, Salmon; J.H. Louk, Michael; Flora Babang, Veramyta Maria Marta; Nenomnanu, Sumarni; D. Nubatonis, Jefrio (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. The aim of this research is to determine the side step and cross step movement abilities of the volleyball game block among students participating in extracurricular activities at PGRI Mnelalete High School, South Central Timor Regency. Materials and Methods. This research uses quantitative descriptive methods with data collection techniques using tests, observations and interviews. The sample in this study was 20 male students of PGRI Mnelalete High School. Results. The results of research on side step and cross step block movement abilities in the men's volleyball game at PGRI Mnelalete High School were in the category